Tortured phrases in sport-related literature - Jaime A. Teixeira da Silva (Bern Open Publishing, 2024)
There is interest in appreciating if 'tortured phrases' (i.e., odd linguistic phrases in scientific literature that purportedly show technical explanations, but which actually are non-sensical or difficult to interpret) exist in the sport literature. To gain an appreciation of this phenomenon, the Tortured Phrases Detector of the Problematic Paper Screener (PPS) was consulted on 9 September 2023), revealing 160 results. After manual screening and filtering, 54 papers related to any aspect of sport (as assessed by papers' titles) were examined, in consultation with their entries at PubPeer (if available) to appreciate the level and extent to which tortured phrases have infiltrated the sport literature. Of the 54 papers examined, 29 were retracted (or withdrawn) to date (6 October 2023), but none indicated tortured phrases as an explicit reason for retraction in their retraction notices. Even though the absolute volume of papers with tortured phrases is tiny relative to the wider body of sport-related literature, that argument is countered by noting that these 54 papers had already collectively been cited 449 times, suggesting that imperfect or fraudulent science tainted by tortured phrases has already begun to permeate the wider sport science literature.